I Need your love: self-stigma and classification of communication patterns required by breast cancer patients - Mohd Jamil, Saidatun Najmiah; Bolong, Jusang; Osman, Mohd Nizam; Tham, Jen Sern (Human Resource Management Academic Research Society, 2022)
Cancer patients desperately require supports from their partners or family members for survival. Various forms of supports either explicitly or implicitly are anxiously needed by them, especially in terms of communication supports to reduce the implications of negative self-stigma faced by them. This article aims to discuss the classification of appropriate communication patterns practiced by spouses and family members of these patients. Researchers suggest that there are four classifications of communication patterns that can be implemented to communicate with breast cancer patients, such as primary communication pattern, secondary communication pattern, linear communication pattern and circular communication pattern. Researchers discovered that these four communication patterns can be practiced by spouses and families of cancer patients to help them control and cope with emotions during treatment.